2008
DOI: 10.1016/j.vetimm.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Avian defensins

Abstract: Modulation of defensin expression may be one way to improve animal health and to reduce zoonotic diseases. Defensins are small, cationic, and amphipathic cysteine-rich antibiotic peptides found in plants, insects, mammals and birds. Whereas alpha- and theta-defensins appear to be absent in birds, several beta-defensins have been isolated from avian heterophils. In addition, beta-defensins were found to be constitutively or inducibly expressed at mucosal surfaces of the respiratory, intestinal and urogenital tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
149
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(163 citation statements)
references
References 130 publications
(171 reference statements)
6
149
0
5
Order By: Relevance
“…Avian ␤-defensins interact electrostatically with negatively charged components of bacterial membranes, such as lipopolysaccharides, lipoteichoic acid, and anionic phospholipids. De- pending on their amino acid composition, AvBDs exhibit more or less antimicrobial activity against a specific bacteria strain (30). In our study, we found that both AvBD11 and AvBD103b exhibited potent antimicrobial activity against the six bacterial strains tested.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Avian ␤-defensins interact electrostatically with negatively charged components of bacterial membranes, such as lipopolysaccharides, lipoteichoic acid, and anionic phospholipids. De- pending on their amino acid composition, AvBDs exhibit more or less antimicrobial activity against a specific bacteria strain (30). In our study, we found that both AvBD11 and AvBD103b exhibited potent antimicrobial activity against the six bacterial strains tested.…”
Section: Discussionmentioning
confidence: 55%
“…AvBDs are small cationic nonglycosylated peptides (1 to 9 kDa). Some of them were successfully tested for their antimicrobial activity, including chicken AvBDs AvBD1, -2, -7, and -9, turkey AvBD1 and -2, ostrich AvBDs AvBD1, -2, -7, and -8, and penguin AvBD103b (3,30). In mammals, ␤-defensins are molecules of innate and adaptive immunity, with a broad spectrum of antimicrobial activity (1).…”
mentioning
confidence: 99%
“…The antimicrobial activity of these ostrich peptides is sensitive to cations (35), and their targets seem to be intracellular (34). In chicken, the ␤-defensin family encompasses 14 genes that have mostly been identified in nucleic acid sequence data (40). The mature peptide of AvBD1 and AvBD2, formerly called gallinacin 1 and gallinacin 2, were the only ones isolated from heterophil granulocytes (7,8).…”
mentioning
confidence: 99%
“…Genetic variants in cytokines and related genes have been associated with numerous Salmonella-resistance phenotypes (85)(86)(87). The antimicrobial b-defensin peptides serve in the innate immune response against bacteria (88). Structural variants in several b-defensin genes were associated with bacterial load in the cecal content or spleen tissue after Salmonella challenge (89).…”
Section: Salmonellamentioning
confidence: 99%